The nature of trusts and the conflict of laws - Agnew, S; McFarlane, B (Sweet and Maxwell, 2021)
Considers, with reference to trusts and other equitable interests, the challenges involved in managing relevant conflicts of laws such as those involving proprietary or relational interpretations of trusts, those between common law and equity, and those between national law and external legal systems. Reviews the methodology adopted, the position prior to Akers v Samba Financial Group (SC), and key aspects of the court's reasoning in Akers.